(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Zakaria Z, Abinawanto, Angio MH, Supriatna J. 2022. Habitat preferences and site fidelity of Tarsius supriatnai in agricultural area and secondary forest of Popayato-Paguat Landscape (Gorontalo, Indonesia). Biodiversitas 23: 3844-3851. Tarsius supriatnai is a new species experiencing a declining population trend due to deforestation. This study aims to determine the microhabitat preferences and site fidelity of T. supriatnai in the agricultural areas and secondary forests of the Popayato-Paguat landscape, Gorontalo, Indonesia. Measuring important value index (IVI) conducted by vegetation analysis of the nest tree location found in the two habitats was carried out using a quadrat method in seedling, sapling, pole, and tree forms. In addition, temperature and light intensity around the nest tree was also measured. The results showed that in the habitat of agricultural areas, the plant with the highest IVI was not the nest tree. Meanwhile, in the secondary forest habitat, the plant with the highest IVI at the tree form (Ficus virens) was the nest tree used by T. supriatnai. The diversity value of the H’ and E index showed that the two habitats were in the high to moderate. There was no significant difference in temperature and light intensity between the two habitat types. The results also showed that T. supriatnai mostly used the nest tree of Bambusa vulgaris (26.32%) in the agriculture area and Schizostachyum lima and Calamus zollingeri (28.57%) in the secondary forest. A survey was conducted to evaluate site fidelity to several nest trees found in 2018. The result revealed that T. supriatnai still uses 42.9% of nest trees.